Towards Networked eHealth: OMaT Project (Phase I) - Muteba A., Eustache (Journal of Health Informatics in Africa, 2014)
Background and Purpose: A longtime ago, malaria was one of the most challenging infectious diseases caused by the parasite called Plasmodium and localized in areas of Asia, Africa, and Central and South America. It has affected developing countries’ human resources and directly lowered its annual economic growth. The project OMaT is an online system, eHealth networked, to assist physicians at medical consultation in order to optimize the quality of care of the patients with malaria disease. Methods: Our clinical decision support system for treatment of malaria is based on consensus guidelines and protocols for the management of malaria. Thus, the system only deals with medical theory and practice identified in advance, limited and structured so for its efficiency and completeness. The OMaT system provides the diagnosis and therapy aids of malaria’s disease. But also, a Geographic Information System database that will store and will provide relevant information on malaria’s patient case of different regions for the optimization of malaria’s treatment. Results: The prototype system presented is related to the phase I of the OMaT project. The proposed solution, in form of web applications includes a Generic Medical Decision Support System and is expected to assist Healthcare Professionals at medical consultation and decision of the patients with malaria disease. The prototype are developed using PHP, XML, HTML, JavaScript and CSS as front end and raw files, MySQL and NoSql Data base as the backend. Conclusions: The OMAT Project under the decision support system is expected to optimize quality of care. The solution we offer meets several requirements such as the reliability of the information entered, protection against handling errors and lack of dangerous results, with respect to confidentiality and anonymity. We envisage again to proceed to the integration of smart technologies that can allow remote clinical examination, complementary examination and tests. Keywords: Optimization of Diagnosis and treatments of Malaria, Networked eHealth and Interoperability, Geographic Information System, Smart healthcare technologies